Türkiye'de Sınırlı Yayılışa Sahip Bir Meşe Türü: Quercus Ilex (Pırnal Meşesi) - (:unkn) unknown (My University, 2003)
0

Quercus ilex which is the natural evergreen oak species occurs in the very limited very areas in the coastal regions of Turkey. It grows within Pinus brutia forests and macciha formations in the humid habitats. This oak species begins at the sea level and rises up to 1100 m altitude in which Mediterranean climatic conditions prevail. In this area Quercus ilex is mostly composed of macchia elements such as Arbutus andrachne, A. unedo, Phillyrea latifolia, Laurus nobilis, Styrax officinalis, Cercis siliquastrum, and Quercus coccifera. Palinological studies on Tertiary flora of Turkey have revealed that Quercus ilex had a wider dispersal area then, and it formed associations in some areas which today do not carry suitable ecological conditions for their growth.